2021
DOI: 10.1111/1365-2656.13636
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating heat stress during development exposes reproductive costs and putative benefits

Abstract: 1. Temperature and thermal variability are increasing worldwide, with well-known survival consequences. However, effects on other potentially more thermally sensitive reproductive traits are less understood, especially when considering thermal variation. Studying the consequences of male reproduction in the context of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…A result was similarly found in D. suzukii males raised at 30°C (Kirk Green et al, 2019) and in line with the idea that spermiogenesis is affected as found previously (Ben‐David et al, 2015) halting the maturation of sperm. However, there is the potential for strong variation across genotypes in their ability to produce mature sperm as indicated by the variation in fertility at sub‐lethal temperatures across isogenic lines of the Drosophila Genetic Reference Panel (Rodrigues et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A result was similarly found in D. suzukii males raised at 30°C (Kirk Green et al, 2019) and in line with the idea that spermiogenesis is affected as found previously (Ben‐David et al, 2015) halting the maturation of sperm. However, there is the potential for strong variation across genotypes in their ability to produce mature sperm as indicated by the variation in fertility at sub‐lethal temperatures across isogenic lines of the Drosophila Genetic Reference Panel (Rodrigues et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary responses to selection can occur if there is heritable variation in heat and cold tolerance and their genetic association is weak or positive. Direct estimates of selection on heat and cold tolerance are, however, rare (20), and estimating its genetic basis is extremely challenging (21)(22)(23). Long-term studies are needed where individuals with known genotypes are repeatedly measured, but this requires a notorious amount of effort (24).…”
Section: Introductionmentioning
confidence: 99%
“…We here investigated the recovery dynamics of a temperate D. melanogaster strain with a special focus on effects on the male reproductive tissues. Overall, sublethal temperatures severely affected a male's ability to reproduce as found in other ectotherms (Conrad et al, 2017;Nguyen et al, 2013;Parratt et al, 2020;Rodrigues et al, 2022Rodrigues et al, , 2021Sales et al, 2018;Vasudeva et al, 2019;Walsh et al, 2019;Zheng et al, 2017;Zwoinska et al, 2020). In accordance with previous findings (Chakir et al, 2002;Petavy et al, 2001), the males used here became temporarily sterile when exposed to temperatures above 29°C during development.…”
Section: Discussionmentioning
confidence: 86%
“…A result similarly found in D. suzukii males raised at 30°C (Kirk Green et al, 2019) and in line with the idea that spermiogenesis is affected as found previously (Ben- David et al, 2015) halting the maturation of sperm. However, there is the potential for strong variation across genotypes in their ability to produce mature sperm as indicated by the variation in fertility at sub-lethal temperatures across isogenic lines of the Drosophila Genetic Reference Panel (Rodrigues et al, 2021).…”
Section: Discussionmentioning
confidence: 99%